Taxonomy and diversity of ants associated with cacao and evaluation of Oecophylla smaragdina Fabricius (Hymenoptera: Formicidae) for biological control of Helopeltis bakeri Poppius (Hemiptera: Miridae) in Quezon and Laguna, Philippines - Pag-Ong, Anthony Ian (Animo Repository, 2021)
The cacao orchard in Quezon Agricultural and Experiment Station (QAES) in Bgy. Lagalag, Tiaong, Quezon Province subjected to two management regimes: properly pruned and weeded [Site 1] versus irregularly pruned and less-weeded [Site 2] yielded 20,682 individual ant samples based on pooled data taken from June 2019 to March 2020 using five sampling techniques, namely, canopy beating, baiting, pitfall trapping, Winkler sack method, and hand-picking collection. Taxonomically, the total ant samples represented 21 species under 21 genera and four subfamilies – Myrmicinae (13,298 individuals representing 8 genera: Carebara, Cardiocondyla, Crematogaster, Monomorium, Pheidole, Solenopsis, Strumigenys and Trichomyrmex in 8 species); Formicinae (6,143 individuals under 4 genera: Nylanderia, Oecophylla, Paratrechina and Polyrhachis in 4 species); Dolichoderinae (1,008 individuals under 3 genera: Tapinoma, Technomyrmex and Dolichoderus in 3 species); and Ponerinae (231 individuals under 6 genera: Diacamma, Hypoponera, Leptogenys, Pachycondyla, Odontomachus, and Odontoponera in 6 species). Irregularly pruned and less-weeded site with 18 species had a more diverse fauna with H1=1.56 and D=0.709 compared to properly pruned and weeded site with H1=1.35 and D=0.655 having 17 species. Sorensen’s index of similarity value (CC=0.8) showed a high species similarity and was supported by the 14 species common in both sites. k-Dominance curve supports the calculated diversity indices showing that Site 2 having a lower height of the curve than Site 1 with a more diverse ant population. On the other hand, the rank abundance curve (Whittaker plot) revealed that both sites have the same evenness, while the rarefaction curve suggests that the maximum available ant species was collected given the efforts made in the collection as its curve yielded an asymptote at the tail-end. For β-diversity, inference coming from the 30 sampling points, considered as local habitats in this study showed a range of moderate (H’= 0.38) to moderately high (H’ = 0.75) diversity of ant population while its species richness shows an ascending graph of the number of species richness. The Formicine, Oecophylla smaragdina Fabricius, ranked 2nd in the total number of individuals. Carebara diversa even though ranked 1st is not arboreal and could not be a potential biological control agent of CMB. O. smaragdina had the highest Levin’s niche breadth measure (B) value of 23.29 and when transformed to a standardized niche breadth, corresponds to a value of (BA) = 0.77, which strongly suggests that O. smaragdina is a high generalist predatory ant. The role of O. smaragdina as a generalist was observed through the high variety of prey and food source. Four foraging techniques, were observed from O. smaragdina: solitary foraging, team transport, group recruitment, and tandem foraging, wherein the first two had the most observed occurrences. Solitary foraging means the ant can successfully hunt singly even on larger prey while team transport shows their effective communication and foraging characteristics. Additionally, O. smaragdina also registered the highest behavioral and numerical dominance in finding and defending a food source using a baiting scoring system, which is a definite behavior of a generalist predator. In the field-cage experiment, the control group, which did not receive any O smaragdina ant nest had feeding lesions to more than 50% of all pods surface, thus, 28 of 30 (93.33%) pods shriveled due to Black Pod Disease as a secondary infection. Whereas, the experimental group only had a 36% feeding lesion on all pods. In the no-choice test feeding experiments, Oecophylla smaragdina and Odontomachus simillimus have been observed to show aggressive behavior towards the cacao pest CMB. However, O. simillimus does mainly nest in the ground and essentially would not forage on flying and arboreal insects such as CMB. With these results, it could be considered that O. smaragdina is a potential biological control agent of CMB.